O trabalho escravo contemporâneo e a atuação da CPT no campo (1970 - 1990) - Silva, Moisés Pereira da (2016)
This text is the result of research on slave labor in the field, in the Araguaia-Tocantins2, and the mediation of the Pastoral Land Commission, between the 1970s and 1995. The interest in understanding the slave labor in the country was born of previous research (Silva 2011) which studied the work of the CPT in land disputes in the Amazon. It was noticed that the occasion was significant efforts of pastoral workers in fighting the slave labor that in the field, was also implicated in the problem of land concentration. The effort, in addition to presenting the slave labor contours, try to identify the mechanisms that prolong their stay in Brazilian society and in this stay, understand the settings of the actions and speeches of mediators in addressing the contemporary slave labor. The role of workers, fleeing farms and denounce, is the action of the substrate of the mediators, also considering that the pastoral workers define their action from the demands of rural workers and squatters. The mobilization of individuals, nations and institutions is strategy of the mediators in the struggle in defense of rural workers. The forms of mediation are diverse, but the visibility of violence in the country was the main strategy to confront this violence